Evaluating the Role of Audit Committees and Internal Auditors in Strengthening Good Corporate Governance: A Case Study of Islamic Bank in Indonesia - Dipradja, Muhammad Hafid Fadhilah; Dipradja, Muhammad Irfan (Journal of Business Management Education (JBME), 2024)
This study examines the role of audit committees and internal auditors in implementing good corporate governance (GCG) at Bank X in 2023. Employing a qualitative approach, it explores how these governance bodies contribute to maintaining transparency, accountability, responsibility, professionalism, and fairness—core principles of GCG. Data were collected through literature reviews, company reports, and interviews with key stakeholders. The findings reveal that both the audit committee and internal auditors play pivotal roles in ensuring regulatory compliance and improving governance practices. While the audit committee functions primarily as an oversight and advisory body, internal audit unit is actively involved in operational audits to identify deviations and recommend improvements. The study underscores the need for continuous improvement in governance practices and highlights areas for future development.